2020
DOI: 10.1111/jopr.13268
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Digital Design of the Occlusal Anatomy of Monolithic Zirconia Crowns Compared to Dental Technicians’ Digital Waxing: A Controlled Clinical Trial

Abstract: Purpose Reconstructing the occlusal morphology of posterior teeth in definitive dental prosthesis can be challenging. The use of the correlation technique enables replication of the information and occlusal anatomy of interim dental prostheses to the definitive ones. The purpose of this controlled clinical trial was to compare the static and dynamic contacts (SDC) of monolithic zirconia crowns designed with correlation and library techniques. Material and Methods Twenty‐four patients were included in the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…During scanning, a dry field was maintained using a dental aspirator. The implant-supported temporary prosthesis was acquired to transfer the vertical dimension, shape, and occlusal morphology to the definitive prosthesis [5]. The 10 STL files were uploaded to CAD software (Exocad, Exocad DentaCad, Darmstadt, Germany) to design the frameworks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…During scanning, a dry field was maintained using a dental aspirator. The implant-supported temporary prosthesis was acquired to transfer the vertical dimension, shape, and occlusal morphology to the definitive prosthesis [5]. The 10 STL files were uploaded to CAD software (Exocad, Exocad DentaCad, Darmstadt, Germany) to design the frameworks.…”
Section: Methodsmentioning
confidence: 99%
“…A decrease in operative time and patient discomfort and increased accuracy represent the main advantages that digital technology has introduced into clinical practice [2,3]. Regarding the digital impression for single crowns [4,5] or three-unit fixed dental prostheses (FDPs) [6], several authors have demonstrated the better performance of a digital workflow. However, discordant opinions have emerged among clinicians and researchers regarding a digital impression for full-arch implant-supported FDPs.…”
Section: Introductionmentioning
confidence: 99%
“…Precise impression making from dental implants is one of the influential factors in achieving passive fit (Alikhasi et al, 2015 ). Inaccurate impressions or prosthetic fabrication can lead to incomplete seating of restoration, which results in insufficient adhesion, microleakage, tooth hypersensitivity, dental caries, need for endodontic treatment, and gingival inflammation (Di Fiore et al, 2019 ; Fathi, Hashemi et al, 2023 ) and inflict delayed pain and discomfort on the patient (Shadmehr et al, 2021 ). Utilizing digital tools has been lucrative in various fields of dentistry including radiology and prosthodontics.…”
Section: Introductionmentioning
confidence: 99%
“…The design of a single crown restoration should be in a functionally and anatomically harmonic relationship with the adjacent and antagonistic teeth [1][2][3][4][5]. The occlusal surface of a single crown should offer functional stability in maximum intercuspation (MICP) and no interference during eccentric movements [6].…”
Section: Introductionmentioning
confidence: 99%